2017
DOI: 10.1038/s41598-017-11867-w
|View full text |Cite
|
Sign up to set email alerts
|

Spraying Brassinolide improves Sigma Broad tolerance in foxtail millet (Setaria italica L.) through modulation of antioxidant activity and photosynthetic capacity

Abstract: To explore the role of Brassinolide (BR) in improving the tolerance of Sigma Broad in foxtail millet (Setaria italica L.), effects of 0.1 mg/L of BR foliar application 24 h before 3.37 g/ha of Sigma Broad treatment at five-leaf stage of foxtail millet on growth parameters, antioxidant enzymes, malondialdehyde (MDA), chlorophyll, net photosynthetic rate (P N), chlorophyll fluorescence and P700 parameters were studied 7 and 15 d after herbicide treatment, respectively. Results showed that Sigma Broad significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…One of their protective mechanisms is the antioxidant system, which is composed of a variety of enzymes, including superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), ascorbate peroxidase (APX) and other enzymes, for protecting against oxidative damage [7]. Antioxidant enzyme activity has been proven to be related to herbicide tolerance in a variety of plants [5,6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…One of their protective mechanisms is the antioxidant system, which is composed of a variety of enzymes, including superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), ascorbate peroxidase (APX) and other enzymes, for protecting against oxidative damage [7]. Antioxidant enzyme activity has been proven to be related to herbicide tolerance in a variety of plants [5,6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Kasajima (2017) found that the treatment of leaves with methyl viologen caused a differential decrease in the Fv/Fm of different varieties of rice leaves. Yuan et al (2017b) reported that treatment with sigma at 3.37 g ha −1 significantly reduced the Y(II) and ETR of foxtail millet and inhibited the PSII activity of foxtail millet. In this study, we found that treatment with pyrazosulfuron-methyl reduced the Fv/Fm, ETR, and qP and increased the qN of foxtail millet leaves, indicating that the PSII reaction center was injured and that the leaf thylakoid membrane was damaged.…”
Section: Discussionmentioning
confidence: 99%
“…The stem diameter was measured with a Vernier caliper. The leaf area was calculated using the following equation (Yuan et al, 2017b): leaf area = 0.75 × leaf length × leaf width…”
Section: Measurementsmentioning
confidence: 99%
“…One of their protective mechanisms is the antioxidant system, which is composed of a variety of enzymes, including superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), ascorbate peroxidase (APX) and other enzymes for protecting against oxidative damage [5]. At present, antioxidant enzyme activity has been proven to be related to herbicide tolerance in a variety of plants [3,4,7,8].…”
Section: Introductionmentioning
confidence: 99%